The English Language and its impact on identities of multilingual Malaysian undergraduates - Lee, Su Kim,; Lee, King Siong,; Wong, Fook Fei,; Azizah Ya’acob, (Penerbit UKM, 2010)
Despite the increasing prominence of English as a world lingua franca, there is little research on how the use of English affects the identities of Malaysian speakers. Asmah Haji Omar observed that interest in language and identity seemed to be confined to studies on national identity. A doctoral study by Lee Su Kim of the identity of Malaysian speakers of English found that there was resentment in certain localized contexts amongst the Malay respondents in the study towards the use of English. Expressions of resentment and ambivalence towards the use of the English language were also prevalent amongst the non-Malay respondents within certain contexts. This paper presents the findings of a qualitative research study which sets out to investigate the impact of English on the identities of young Malaysian undergraduates in selected private and public universities in Malaysia. Using qualitative methods, this research study essentially takes off from Lee Su Kim’s doctoral research study, and aims to explore on a larger scale the role of English in the identity construction of a younger Malaysian cohort from both public and private universities. The findings presented here are from a few selected case studies that provide the qualitative data. The discussion will focus on how different multilingual Malaysian undergraduates regard English vis a vis the other languages in their repertoire and how it has affected their identity constructions and everyday negotiations. Three dominant themes arising from the findings will be discussed, 1) Multilingualism with English emerging as the dominant language, 2) English viewed as a pragmatic language and a language of empowerment, and 3) Varying degrees of ‘othering’.